Spine slenderness is not an early sign of progression in adolescent idiopathic scoliosis. (October 2022) - Vergari, Claudio; Skalli, Wafa; Abelin-Genevois, Kariman; Bernard, Jean-Claude; Hu, Zongshan; Cheng, Jack Chun Yiu; Chu, Winnie Chiu Wing; Assi, Ayman; Karam, Mohammad; Ghanem, Ismat; Bassani, Tito; Galbusera, Fabio; et al.
Highlights: Slenderness of a rod is a measurement of structural instability in compression. Adolescent idiopathic scoliosis patients have more slender spine than asymptomatic. Slenderness does not appear to be an early sign of scoliosis progression. Abstract: Adolescent idiopathic scoliosis (AIS) is a three-dimensional deformity of the spine. Spine slenderness, which represents its potential instability to buckling under compressive loads, was shown to be higher in AIS patients than non-scoliotic subjects, but it is not clear at what stage of the progression this difference appeared, nor if slenderness could be used as an early sign of progression. In this study, we hypothesized that slenderness could be an early sign of progression. One-hundred thirty-eight patients and 93 non-scoliotic subjects were included. They underwent standing biplanar radiography and 3D reconstruction of the spine, which allowed computing vertebra and disc slenderness ratio. Then, patients were followed until progression of the deformity or skeletal maturity (stable patients). Vertebral slenderness ratio in AIS patients varied between 2.9 [2.7; 3.0] (T9) and 3.4 [3.2; 3.6] (T1), while disc slenderness ranged from 0.6 [0.6; 0.7] at T6-T7 to 1.2 [1.1; 1.3] at L4-L5. Slenderness ratio increased with age, while disc slenderness tended to decrease with age and Cobb angle. Slenderness was similar between progressive and stable patients, and also between patients and non-scoliotic subjects. In conclusion, spinal slenderness does not appear to be an early sign of progression. Further studies should analyse the development of slenderness during growth, and how it could be affected by non-operative treatment.